Design and synthesis of potent substrate-based inhibitors of the Trypanosoma cruzi dihydroorotate dehydrogenase. Issue 4 (15th February 2017) - Inaoka, Daniel Ken; Iida, Maiko; Hashimoto, Satoshi; Tabuchi, Toshiyuki; Kuranaga, Takefumi; Balogun, Emmanuel Oluwadare; Honma, Teruki; Tanaka, Akiko; Harada, Shigeharu; Nara, Takeshi; Kita, Kiyoshi; Inoue, Masayuki
Graphical abstract: Abstract: Chagas disease, caused by the parasitic protozoan Trypanosoma cruzi, is the leading cause of heart disease in Latin America. T. cruzi dihydroorotate dehydrogenase (DHODH), which catalyzes the production of orotate, was demonstrated to be essential for T. cruzi survival, and thus has been considered as a potential drug target to combat Chagas disease. Here we report the design and synthesis of 75 compounds based on the orotate structure. A comprehensive structure-activity relationship (SAR) study revealed two 5-substituted orotate analogues (5u and5v ) that exhibit K i app values of several ten nanomolar level and a selectivity of more than 30, 000-fold over human DHODH. The information presented here will be invaluable in the search for next-generation drug leads for Chagas disease.